2008
DOI: 10.1080/07370020802278254
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Analytical Usability Evaluation Methods: A Case Study

Abstract: Analytical usability evaluation methods (UEMs) can complement empirical evaluation of systems: for example, they can often be used earlier in design, and can provide accounts of why users might experience difficulties, as well as what those difficulties are. However, their properties and value are only partially understood. One way to improve our understanding is by detailed comparisons using a single interface or system as a target for evaluation, but we need to look deeper than simple problem counts: we need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 67 publications
(72 reference statements)
1
16
0
Order By: Relevance
“…[10] is a methodology developed to address specifically the evaluation of usability of multi-modal systems. The scope of the methodology extends to issues related to user knowledge and use in context, with a special focus on the issues concerned with the physical relationship between the user and the device [1]. Multimodal interfaces can enhance the user's understanding, as they provide more communication channels between the user and the system.…”
Section: Uan (User Action Notation)mentioning
confidence: 99%
See 1 more Smart Citation
“…[10] is a methodology developed to address specifically the evaluation of usability of multi-modal systems. The scope of the methodology extends to issues related to user knowledge and use in context, with a special focus on the issues concerned with the physical relationship between the user and the device [1]. Multimodal interfaces can enhance the user's understanding, as they provide more communication channels between the user and the system.…”
Section: Uan (User Action Notation)mentioning
confidence: 99%
“…Various case studies are reported in the literature with regard to the evaluation of usability methods ( [18], [1], [12], [4], [6]). Comparisons between methods have been carried out in terms of problem count, scope, validity, evaluator effect, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Methods must be chosen to provide leverage on the issues a client faces (Blandford et al 2008) within the constraints of the project. For example, workload methods should be chosen for workload problems, and analytic rather than empirical methods may be selected if the project is fast and cheap.…”
Section: Developing Analytic Insight and Project Understandingmentioning
confidence: 99%
“…In particular, clashes between modalities, integration of information, and possible lost information can be identified through an EMU analysis. Earlier studies have shown that EMU is learnable [10] and that it occupies a particular niche within the space of analytical evaluation methods [1]. However, the initial study of EMU in use highlighted the fact that the process of conducting an analysis was unduly laborious.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical data of the arm in use was also analysed. A full account of this study is presented by Blandford et al [1]. In brief, the analysis showed that EMU occupies a useful niche in the repertoire of evaluation techniques.…”
Section: Utility Evaluation Of Emumentioning
confidence: 99%